Prospects and applications of plant growth promoting rhizobacteria to mitigate soil metal contamination: A review. (May 2020) - Guo, JunKang; Muhammad, Haris; Lv, Xin; Wei, Ting; Ren, XinHao; Jia, HongLei; Atif, Saleem; Hua, Li
Abstract: The rapid increase in world population has generated the issues of hunger, poverty, food insecurity and malnutrition. To meet the challenge of increased food production of better quality, the farmers were compelled to use more chemical fertilizers, especially in developing countries. The higher use of chemical fertilizers interrupts the food chain through eutrophication, the polluting air and soil by incorporating metals. Trace metals have a deleterious effect on soil microbial and plant growth. To minimize metal toxicity and maximize the production of food, there are different approaches that can lead to lessen the use of chemical fertilizers. Plant growth promoting rhizobacteria (PGPR) are capable to enhance the plant growth and can remediate metal contaminated soils. PGPR has the ability to improve food production with diverse attributes e.g. producing siderophores that promote rhizosphere trace metal sequestration and production of organic and inorganic acids thus affecting trace metal bioavailability and plant induced systemic tolerance (IST) to limit the crop metal accumulation. In this review paper, we have discussed the biological approach which is environmentally friendly and cost-effective mean for metal polluted soils and gives some new insights for safety use of PGPR in trace metal contaminated fields. Graphical abstract: Image 101 Highlights: Chemical fertilizers are one of the greatest source of metals loading into soil. Use of excessive fertilizer can compromise the integrity of the water quality and soil properties. PGPR can be an absolute approach to remediate metal contaminated soils. Plants have induced an effective resistance to abiotic stresses by PGPR. Role of ACCD with other PGP traits.